2002
DOI: 10.1016/s0008-6363(02)00334-6
|View full text |Cite
|
Sign up to set email alerts
|

Exercise induces early and late myocardial preconditioning in dogs

Abstract: Objective: We tested the hypothesis that exercise induces myocardial preconditioning in dogs. Methods: We instrumented dogs with a snare on the anterior descending coronary artery and catheters in the root of the aorta, left ventricular cavity and coronary sinus. After recovering from surgery the dogs were trained to stay in the laboratory and run on a treadmill. Subsequently, they were randomly allocated to five groups: (1) non-preconditioned dogs: under anesthesia, the anterior descending coronary artery was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
95
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(100 citation statements)
references
References 21 publications
5
95
0
Order By: Relevance
“…Experiments in pigs 14 and dogs 15 showed that brief episodes of tachycardia that do not induce ischemia before a prolonged coronary occlusion decrease the infarct size (Figure) by a mechanism similar to that of ischemic preconditioning and that is mediated through modifications of sarcoplasmic reticulum and mitochondrial ATPsensitive potassium channels. 16,17 Subsequent experiments in rats 18 and in dogs 19 showed, as expected, that brief episodes of exercise also induced preconditioning of the infarct size. Interestingly, exercise induces early as well as late preconditioning and the magnitude of reduction in infarct size observed in dogs is much larger than that obtained with ischemic and tachycardia preconditioning (Figure).…”
Section: Benefits Of Exercisementioning
confidence: 55%
“…Experiments in pigs 14 and dogs 15 showed that brief episodes of tachycardia that do not induce ischemia before a prolonged coronary occlusion decrease the infarct size (Figure) by a mechanism similar to that of ischemic preconditioning and that is mediated through modifications of sarcoplasmic reticulum and mitochondrial ATPsensitive potassium channels. 16,17 Subsequent experiments in rats 18 and in dogs 19 showed, as expected, that brief episodes of exercise also induced preconditioning of the infarct size. Interestingly, exercise induces early as well as late preconditioning and the magnitude of reduction in infarct size observed in dogs is much larger than that obtained with ischemic and tachycardia preconditioning (Figure).…”
Section: Benefits Of Exercisementioning
confidence: 55%
“…The velocity on the treadmill was 15 m/min and the exercise duration was for 10-20 min/day. The EP protocol was designed with minor modifications of the protocol described by Domenech et al 10 and Parra et al 6 On the seventh day, animals were randomly assigned to 10 experimental groups (n=25 rats per group):…”
Section: Experimental Protocolmentioning
confidence: 99%
“…These authors reported in conscious rabbits that a brief episode of cardiac pacing (500 beats per minute for 5 min) reduced post-pacing ST-segment elevation and decreased left ventricular end-diastolic pressure for up to 1 h following which the beneficial effects disappeared and re-appeared 24 and 48 h later, with the beneficial effect finally disappearing again after 72 h [5], a timeline which closely matched delayed IPC. Exercise has also been reported to elicit delayed preconditioning with myocardial infarct-size reduction 24 h later in both rats [9] and dogs [10]. In terms of the elucidating the mechanisms underlying delayed preconditioning much of the work has focused on ischemia rather than pacing or exercise as the stimulus for delayed cardioprotection.…”
Section: Characteristics Of Delayed Preconditioningmentioning
confidence: 99%